2018
DOI: 10.15625/2525-2518/55/4c/12123
|View full text |Cite
|
Sign up to set email alerts
|

Research on Harvesting of Microalgae Chlorella Sp. By Electrochemical Flotation Method Using Corrosive Electrodes

Abstract: Microalgae are a promising feedstock for biodiesel production. Harvesting of microalgal biomass is still a bottleneck to its commercial scale application, due to small cell size, low culture densities, colloidal stability and thus economic disadvantage. The aim of this study was to evaluate the biomass separation of the small size microalgae Chlorella sp. by electrochemical flotation process with rectangle electrodes using aluminum or iron plates. The most effective conditions for this experiment involved the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The study demonstrated that by utilizing a current density of 1.5 mA/cm 2 for 30 min, Al was more beneficial to the electroflotation process than Fe as 90% of microalgae was harvested with the former. Additionally, 0.74-1.5 g/L concentration of microalgal biomass was harvested in this study with a power consumption of 1.36 kWh/kg [92]. Further, Estupinan et al (2018) designed a unique electroflotation system for the effective harvesting of freshwater microalgae as well as to increase the biomass concentration.…”
Section: Modified Electroflotation To Improve Biomass Productionmentioning
confidence: 90%
“…The study demonstrated that by utilizing a current density of 1.5 mA/cm 2 for 30 min, Al was more beneficial to the electroflotation process than Fe as 90% of microalgae was harvested with the former. Additionally, 0.74-1.5 g/L concentration of microalgal biomass was harvested in this study with a power consumption of 1.36 kWh/kg [92]. Further, Estupinan et al (2018) designed a unique electroflotation system for the effective harvesting of freshwater microalgae as well as to increase the biomass concentration.…”
Section: Modified Electroflotation To Improve Biomass Productionmentioning
confidence: 90%